2013
DOI: 10.1186/1753-2000-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, anxiety and depression in young adults with disability benefits due to childhood-onset somatic conditions

Abstract: BackgroundAs the treatment of chronic or life-threatening diseased children has dramatically over recent decades, more and more paediatric patients reach adulthood. Some of these patients are successfully integrating into adult life; leaving home, developing psychosocially, and defining a role for themselves in the community through employment. However, despite careful guidance and support, many others do not succeed. A growing number of adolescents and young adults who have had a somatic disease or disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…International Journal of Adolescence and Youth 7 Therefore, youth living with a CC seems to be at higher risk for psychological wellbeing. These data support the suggested hypothesis in this study and reported in the literature, indicating that adolescents living with a CC can have increased vulnerability for an emotional and psychological healthy development (Bernstein et al, 2011;Verhoof et al, 2012), presenting more internalised symptoms, such as depression (Miyazaki et al, 2006;Vanhalst et al, 2013) and anxiety (Lavigne & Faier-Routman, 1992), and this can continue as a risk factor for later in adulthood (Verhoof et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…International Journal of Adolescence and Youth 7 Therefore, youth living with a CC seems to be at higher risk for psychological wellbeing. These data support the suggested hypothesis in this study and reported in the literature, indicating that adolescents living with a CC can have increased vulnerability for an emotional and psychological healthy development (Bernstein et al, 2011;Verhoof et al, 2012), presenting more internalised symptoms, such as depression (Miyazaki et al, 2006;Vanhalst et al, 2013) and anxiety (Lavigne & Faier-Routman, 1992), and this can continue as a risk factor for later in adulthood (Verhoof et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…In Portugal, the studies Health Behaviour School-Aged Children (HBSC) (Matos & Equipa Aventura Social, 2000 and Kidscreen (Gaspar & Matos, 2008) have been also pointing out higher vulnerability in this population. Living with a CC while growing up may also contribute for worse health-related quality of life and symptoms of anxiety and depression in young adults (Verhoof, Maurice-Stam, Heymans, & Grootenhuis, 2013), placing them at higher risk for poor vocational/educational and social outcomes (Maslow, Haydon, McRee, Ford, & Halpern, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In 377 young adults aged 22-31 years who have grown up with a somatic condition there was worse QoL and feelings of anxiety (29.7 %) and depression (17 %) in those claiming disability benefits [63]. The author suggests that future research might need to focus on emotional functioning and specific psychosocial support aimed at workforce participation.…”
Section: Youth Workmentioning
confidence: 99%
“…Disabled adolescents are less satisfied with their lives and school activities (satisfaction), have less positive feelings about life, are socially less active (Well-being), and show less feelings of being included (Social belonging) in comparison to their healthy peers [8]. Some studies showed that people with physical mobility disability reported worse Quality of life than the reference group and a higher percentage were at a risk of anxiety and depressive disorder [9].…”
Section: Introductionmentioning
confidence: 99%